The Meaning of Profit for Traditional Lombok Weavers - Meta Maulina; Yusli Mariadi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The aim of this study is to uncover the meaning of profit from the perspective of traditional textile weavers. The research was conducted qualitatively, using phenomenology as the method. Data collection techniques were done through observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of compiling, disassembling, reassembling, interpreting, and concluding. The study results show that profit, from the perspective of traditional fabric weavers, is understood in two ways: material and non-material benefits. Material benefits are interpreted as savings and deposits to meet daily needs, finance children's education, pay installments, and increase business capital. Non-material benefits are understood as inner satisfaction, a sense of gratitude, and the advantage of being able to get married. Keywords: profit, phenomenology, traditional fabric, ability to marry.